Sistem Informasi Penjualan Berbasis Website untuk Optimalisasi UMKM pada MusiCraft di Kota Palembang - Agustina, Geby Ayu; Heryati, Agustina; Coyanda, John Roni; Afriyani, Fauziah (Jurnal Ilmiah Informatika Global, 2025)
The advancement of information technology has created significant opportunities to enhance efficiency and modernization, including in the Micro, Small, and Medium Enterprises (MSME) sector. MusiCraft, an MSME in Palembang, is engaged in woven crafts and food products, but faces various operational challenges, including manual sales methods, traditional transaction recording, and limited product promotion. This study aims to design and develop a web-based sales information system to address these challenges. Through this system, customers can easily access product information, make purchases, and utilize modern payment methods. For business operators, the system offers features for stock management, automatic transaction recording, and a customer loyalty program that rewards customers. The research employs the Research and Development (R&D) method with a prototype approach, involving users to ensure the system meets their needs. The study results indicate that the web-based information system enhances operational efficiency, expands market reach, and strengthens MusiCraft’s competitiveness in the digital era. The implementation of this system is expected to support MSME sustainability and provide a better shopping experience for customers.